2023
DOI: 10.1021/acs.orglett.3c02577
|View full text |Cite
|
Sign up to set email alerts
|

Base/Solvent Controlled Divergent Synthesis of Norbornane-Fused Dihydrophenanthrenes and Triphenylenes via Palladium Catalyst

Maryam Dehghan,
Mehran Ghasemi,
Farnaz Jafarpour
et al.

Abstract: A base/solvent controlled divergent synthesis for the construction of polycyclic hydrocarbons has been developed. In this process, norbornene through a reagent role leads to the synthesis of norbornane-fused dihydrophenanthrenes, which are essential due to their biological activities. Amazingly, by switching solvent and base, the role of norbornene becomes limited to a mediator/catalyst; therefore, it is removed from the final scaffold, and triphenylenes are regioselectively synthesized. Additionally, by remov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…In the reaction, the aryl norbornyl palladacycle formed by an oxidative addition/norbornene (NBE) insertion/C–H bond activation sequence is the key intermediate. Recently, Kwong et al and our group found that the palladacycle formed by Catellani strategy could be captured by o -bromobenzoic acids to give phenanthrenes and triphenylenes. , Since then, a series of decarboxylative cyclization reactions were reported by us and others via a carboxyl-assisted palladacycle capture strategy, which provide an efficient platform for the synthesis of polycyclic compounds. Despite great progress, the application of α-oxocarboxylic acids in the Catellani reaction has not been reported yet.…”
mentioning
confidence: 99%
“…In the reaction, the aryl norbornyl palladacycle formed by an oxidative addition/norbornene (NBE) insertion/C–H bond activation sequence is the key intermediate. Recently, Kwong et al and our group found that the palladacycle formed by Catellani strategy could be captured by o -bromobenzoic acids to give phenanthrenes and triphenylenes. , Since then, a series of decarboxylative cyclization reactions were reported by us and others via a carboxyl-assisted palladacycle capture strategy, which provide an efficient platform for the synthesis of polycyclic compounds. Despite great progress, the application of α-oxocarboxylic acids in the Catellani reaction has not been reported yet.…”
mentioning
confidence: 99%